Influence of Pomegranate Appearance Attributes on Consumer Choice, and Identification of Barriers and Drivers for Consumption - Pons-Gómez, Ana; Albert-Sidro, Carlos; Bartual, Julián; Yuste, Ferrán; Besada, Cristina (MDPI, 2024)
In a prepurchase situation, consumers base their choice decision on external fruit characteristics, from which they infer internal characteristics. This study investigates consumer preference for pomegranate appearance using a choice-based conjoint analysis with 320 participants. We created 27 images of pomegranates that differed in varietal characteristics: colour (yellow, bicoloured, and red), shape (round, oval, and flattened), and calyx shape (open, semi-open, and closed). Colour was by far the most important factor for consumers, followed by fruit shape and calyx shape. Two preference profiles were identified. Most consumers liked bicolour and red pomegranates equally, and rejected yellow ones, while a smaller group concentrated their choice on bicolour pomegranates. In terms of fruit and calyx shape, oval and flattened fruit and open calyx were the most preferred by both consumer groups. Barriers and drivers for consumption were also investigated. There is still plenty of room to increase pomegranate consumption. Greater availability of pomegranates and ready-to-eat arils in grocery shops, obtaining new unseeded/easier-to-peel varieties, and providing a sensory label would help to overcome current barriers. Marketing campaigns should focus on a pomegranate’s health benefits and its versatility in consumption